Dynamic Level Adjustment For Descriptive Writing With Web Simulation In EFL Teaching - irwan sumarsono; Radina Anggun Nurisma; Akbar Widyoseno (Universitas Islam Madura, 2018)
Concerning English as one of the essential factors to gain access to global information and knowledge of science and technology, the mastery of English writing skills is considered to be necessary in the world of communication. Learning media has an important role in English for Specific Purposes (ESP) context. This study aims to generate product in the form of application on web-based simulation. In this study, learning activity is done through web-based application. This application uses the Dynamic Level Adjustment method which is still Progression or Level-based so the further development is required.to be able to adjust the level of user intelligence. Research and development (R&D) is a method used in this study. The research was conducted through several stages: (1) needs analysis, (2) production planning, (3) development of instructional media, (4) evaluation and revision, (5) field trial to students, (6) final revision. The development of this application is expected to be used as one of the effective teaching materials to facilitate teachers in the learning process and increase learners’ motivation to write. Furthermore, this application has an important role to make learning activities more interesting, practical and accessible for students. Students will be trained to use apps appropriately. Keywords: descriptive writing, web application, ESP Abstrak Pentingnya Bahasa Inggris sebagai salah satu faktor dalam keberhasilan mengakses informasi dan pengetahuan global akan ilmu pengetahuan dan teknologi, menyebabkan pentingnya penguasaan kemampuan menulis dalam Bahasa Inggris dalam dunia komunikasi. Media pembelajaran mempunyai peranan penting dalam kontek Bahasa Inggris ESP. Studi ini dilaksanakan dengan tujuan untuk menghasilkan produk aplikasi berbasis web, yang menggunakan metode Dynamic Level Adjustment yang masih berbasis Progresi atau Level, sehingga pengembangan selanjutnya diharapkan bias disesuaikan dengan tingkat inteligensi penggunanya. Studi ini juga menggunakan Research and Development (R&D). Studi ini dilaksanakan melalui beberapa tahapan : 1) adanya analisa, 2) perencanaan produksi, 3) pengembangan media instruksi, 4) evaluasi dan revisi, 5) uji coba, dan 6) revisi akhir. Pengembangan aplikasi ini diharapkan dapat digunakan sebagai salah satu material pengajaran yang efektif dalam memfasilitasi guru/dosen dalam proses belajar mengajar dan meningkatkan motivasi peserta didik untuk menulis dalam Bahasa Inggris. Aplikasi ini mempunyai peran penting dalam membuat aktifitas belajar menjadi lebih menarik, praktis dan mudah diakses oleh peserta didik. Peserta didik akan diberikan pelatihan penggunaan aplikasi ini.